Cognitive Strategies and Vocabulary Retention in Islamic Boarding School EFL Contexts - Miftahul Rahma; Magdahalena Tjalla; Arqam; Abdul Haris Sunubi; Ambo Dalle (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates the effect of cognitive learning strategies on vocabulary retention and retrieval among EFL learners in an Islamic boarding school context. While previous studies have explored cognitive strategies in general EFL settings, limited research has specifically examined their combined effects on both vocabulary retention and retrieval within Islamic boarding school contexts. The research addressed two main questions: to what extent cognitive learning strategies influence students’ vocabulary retention and how these strategies affect vocabulary retrieval. The study employed a quantitative pre-experimental design using a one-group pre-test and post-test approach. The participants consisted of 30 third-grade students at Pendidikan Diniyah Formal Ulya Putri Sengkang. Data were collected using a structured vocabulary test measuring both retention (recognition and recall) and retrieval (productive use). The data were analyzed using descriptive statistics and paired sample t-tests to determine the significance of improvement. The findings showed a substantial increase in both vocabulary retention and retrieval scores, with the mean retention score improving from 29.47 to 42.83 and retrieval from 25.43 to 42.10. The results also indicated that retention gains were slightly more consistent than retrieval improvements, although both were statistically significant (p < 0.05). These findings suggest that cognitive learning strategies effectively enhance both the storage and active use of vocabulary. The study contributes to cognitive learning theory by reinforcing the role of encoding, storage, and retrieval processes, and offers practical implications for integrating structured cognitive strategies into EFL instruction to improve vocabulary learning outcomes.